Detection of Thrombin Using Label-Free Electrochemical Aptamer Sensor Based on Bimetallic Pd-Au Nanoparticles - Shen, G.Y.; Zhang, S.B.; Hu, X.; Xiao, A.G. (Asian Journal of Chemistry, 2014)
In this paper, we reported a novel label-free electrochemical aptamer sensor based on the catalytic activity of Pd-Au nanoparticles towards H2O2 for the thrombin detection. In the sensing strategy, the Au electrode was first modified with Pd-Au-chitosan film and then the aptamer was immobilized on the surface of Pd-Au nanoparticles. In the presence of thrombin, the aptamer on the surface of the modified electrode would capture thrombin on the electrode interface, which makes a barrier to electro-transfer, resulting in the decreased cyclic voltammetry signals. Using this strategy, thrombin was detected within the range from 0.1 to 25 nM with a detection limit of 0.06 nM (S/N = 3). The aptamer sensor had a good specificity, stability and reproducibility. This simple strategy may pave a way to fabricate a simple aptamer sensors in clinical application.